The Role Of Leadership Style On Work Achievement Tax Volunteer - Galih Wicaksono; Samsiah Samsiah; Imron Imron; Antoni Ludfi Arifin (Educoretax, 2022)
The tax volunteer program is issued by the Directorate General of Taxes in order to assist the fulfillment of tax obligations, especially when reporting individual and corporate tax returns. The volunteers involved were mostly students and members of the tax center from universities. This study aims to determine the effect of leadership style on the work performance of tax volunteers. The population in this study are tax volunteers from universities, while the population is tax volunteers who have served in the Jakarta and Jember areas. This study resulted in the finding that leadership style has a significant and positive effect on the work performance of tax volunteers. The implication is that interested parties should instill a leadership spirit for tax volunteer members.